Optimizing Inventory Systems with RFID: A Narrative Review of Integration, Efficiency, and Barriers - Budiyanto, Albert; Muslim, Muhammad (Sinergi International Journal of Logistics, 2024)
Radio Frequency Identification (RFID) technology has emerged as a transformative solution in modern inventory management, enabling real-time tracking, improved data accuracy, and enhanced operational efficiency. This narrative review investigates the current state of RFID adoption across sectors, focusing on its integration with advanced technologies such as the Internet of Things (IoT), artificial intelligence (AI), and blockchain. Literature was collected using a systematic search of reputable academic databases including Scopus, IEEE Xplore, and ScienceDirect, with keyword combinations designed to capture diverse applications of RFID in inventory systems. The findings reveal substantial benefits, including reductions in manual processing time, improved inventory accuracy, and enhanced traceability. Sector-specific applications in healthcare, pharmaceuticals, and food logistics demonstrate measurable gains in compliance and supply chain transparency. Moreover, RFID’s integration with emerging technologies facilitates predictive analytics and real-time environmental monitoring. However, technical, organizational, and economic barriers continue to hinder broader implementation. These include interoperability issues, resistance to change, and high initial costs. Policy recommendations include the promotion of standardization, investment in infrastructure, and workforce training. Future research should address longitudinal outcomes and explore scalable adoption strategies, particularly for small-to-medium enterprises. Overall, RFID technology represents a strategic innovation poised to revolutionize inventory management through enhanced efficiency, resilience, and adaptability.